2016
DOI: 10.1159/000446530
|View full text |Cite
|
Sign up to set email alerts
|

Shooting for the Moon or Flying Too Near the Sun? Crossing the Value Rubicon in Precision Cancer Care

Abstract: In his last two State of the Union addresses, President Barack Obama has focused on the need to deliver innovative solutions to improve human health, through the Precision Medicine Initiative in 2015 and the recently announced Cancer Moonshot in 2016. Precision cancer care has delivered clear patient benefit, but even for high-impact medicines such as imatinib mesylate (Glivec) in chronic myeloid leukaemia, the excitement at the success of this practice-changing clinical intervention has been somewhat tempered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…It is thought that further research into these areas could unlock new and more costeffective opportunities for radiation therapy to improve outcomes from cancer. In addition, it would help to ensure that radiation therapy continues to be relevant and that research in this area is prioritized in an era of precision medicine, which is increasingly drug-focused (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…It is thought that further research into these areas could unlock new and more costeffective opportunities for radiation therapy to improve outcomes from cancer. In addition, it would help to ensure that radiation therapy continues to be relevant and that research in this area is prioritized in an era of precision medicine, which is increasingly drug-focused (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Previous analyses have indicated that oncology is the most expensive R&D medicines domain, and companies’ strategies are predicated on driving premium pricing, i.e. what the markets will bear, commercial approaches that threaten to undermine healthcare budgets [ 2 , 27 , 28 ]. Our data for oncology medicines from 56 companies over a 24-year period suggest that in the case of precision oncology medicines, this need not be the case.…”
Section: Discussionmentioning
confidence: 99%
“…This product named as Cx601 by Takeda and TiGenix has received orphan status by the Swiss Agency for Therapeutic Products (Swissmedic) for the rare disease. While these innovations are taking place at immense pace, there is growing requirement of policymakers to be engaged along with patients' community to see how best a value-based frameworks and be drawn as rational approaches to use these expensive novel therapeutic modalities in patient care [98].…”
Section: Current Advances and Future Prospectsmentioning
confidence: 99%